AKTIVITAS ANTIOKSIDAN LIP BALM EKSTRAK ETANOL BUNGA KECOMBRANG (Etlingera elatior (Jack) R.M.S.m) - Yahdian Rasyadi; Diana Agustin; Gina Aulia (Jurnal Insan Farmasi Indonesia, 2022)
Kecombrang flower (Etlingera elatior (Jack) R.M.Sm.) has antioxidant compounds that can be used as active ingredients in lip balm cosmetics for lip care. Lipbalm preparations containing 0% (F0), 0.5% (F1), 1% (F2), and 1.5% (F3) ethanol extracts of kecombrang flowers were prepared. The purpose of this study was to examine the antioxidant activity of lipbalm ethanol extract of kecombrang flowers F0, F1, F2, F3. The antioxidant activity of all formulas was carried out using the DPPH method. The results of the antioxidant activity test showed that the IC50 values ??for F0, F1, F2, and F3 were 252.38 g/mL, 235.93 g/mL, 230.79 g/mL, and 219.60 g/mL, respectively. it can be concluded that all lipbalm formulas of kecombrang flower ethanol extract (Etlingera elatior) 0% (F0), 0.5% (F1), 1% (F2), 1.5% (F3) have weak antioxidant activity.